The Dangerous Of Using Food Preservatives To Human Health: A Review - Tampubolon, Manuppak Irianto; Silitonga, Desni Rinanda; Ginting, Grace Anastasia br.; Berkat, Syukur; Sahputri, Cut Juliana; Ghifran, Muhammad Al; Marbun, Eva Diansari (CV. Nusantara Scientific Medical, 2025)
The use of formalin as a food additive remains a recurring issue in processed food products in Indonesia, particularly in perishable items such as wet noodles and tofu. This review examines ten published studies that investigated formalin detection across different regions of Indonesia using a range of analytical approaches, including the Nash reagent, UV-Vis spectrophotometry, rapid test kits, KMnO₄, Tollens reagent, and natural indicators. The findings reveal considerable regional variation in contamination levels, with positive results most frequently reported in Palembang, Yogyakarta, Tomohon, and Pringsewu, while samples from West Jakarta and Sorong were predominantly negative. Among the methods reviewed, the Nash reagent and UV-Vis spectrophotometry demonstrated higher accuracy and sensitivity, whereas simpler techniques were more appropriate for preliminary screening and public education. Overall, this review highlights the need for strong coordination between regulatory oversight, public awareness initiatives, and the availability of reliable detection methods to improve food safety in Indonesia.